Sex and Gender Differences in Fibromuscular Dysplasia - Marianne H Khoury; Sims Hershey; Rebecca M LeLeiko (US Cardiology Review)
Fibromuscular dysplasia (FMD) is a non-atherosclerotic, non-inflammatory vascular disease that was once underrecognized and is significantly more prevalent in women than men. Although it most commonly affects the renal and extracranial carotid arteries, FMD can affect any vascular bed. Complications of FMD can include hypertension, dissection, and stroke. Presentation may vary between the sexes, with male patients having an increased frequency of arterial dissection and aneurysms compared with female patients. Diagnosis requires a high index of suspicion by the treating physician. Several imaging studies can assist with diagnosis, and treatment focuses on the monitoring of affected vessels and intervention only as needed. Antiplatelet therapy for prevention of thrombotic complications is recommended. Studies are still underway to examine the genetic underpinnings of FMD pathophysiology and to evaluate the underlying mechanism of this disease that affects more female than male patients.